Closing the Gap: Structural Evidence for the Missing Hexabromide Dianion [Br6]2−. Issue 5 (10th January 2018) - Sonnenberg, Karsten; Pröhm, Patrick; Müller, Carsten; Beckers, Helmut; Steinhauer, Simon; Lentz, Dieter; Riedel, Sebastian
Abstract: The formation and experimental characterization of the first hexabromide dianion is presented. This dianion fills the last remaining gap in the series of polybromides from the tribromide [Br3 ] − to the undecabromide [Br11 ] − . The experimental results are compared to quantum‐chemical calculations. These calculations predict—based on electrostatic interactions—a T‐structure for the hexabromide dianion, while halogen–halogen bonding favors the hockey‐stick‐like structure experimentally found in the crystal structure. The hexabromide is built of two tribromide moieties, one of which is highly asymmetric. The classification of this unique anion as hexabromide dianion is discussed. The counter ion [C5 H10 N2 Br] + stabilizes the hexabromide dianion by additional σ‐hole interactions. The compound is fully characterized by mass spectrometry, NMR‐, IR and single crystal Raman spectroscopies as well as single‐crystal X‐ray diffraction. Abstract : For a long time, the missing hexabromide dianion [Br6 ] 2− left a gap in the series of polybromides between the tribromide [Br3 ] − and the undecabromide [Br11 ] − . Finally, we were able to stabilize the interaction of two tribromide moieties forming the hexabromide found in [C5 H10 N2 Br]2 [Br6 ]. The compound is fully characterized by mass spectrometry, NMR‐, IR and single crystal Raman spectroscopy as well as single‐crystal X‐ray diffraction.